Pengaruh Kepemimpinan dan Kompensasi Terhadap Kinerja Pegawai DPRD Kabupaten OKU - Yolandre Yolandre; Fifian Permata Sari; Rini Efrianti (SENTRI: Jurnal Riset Ilmiah, 2026)
This study aimed to analyze the influence of leadership and compensation on the performance of employees at the Regional House of Representatives (DPRD) of Ogan Komering Ulu (OKU) Regency. Employee performance is an important factor in supporting the effectiveness and efficiency of organizational activities; therefore, effective leadership and appropriate compensation are expected to improve work productivity. The study was conducted in February 2026 using a quantitative descriptive research method. A census sampling technique was employed, in which all 31 employees of the DPRD of OKU Regency were selected as the research sample. Data were collected through questionnaires and analyzed using multiple linear regression to determine the effect of leadership and compensation on employee performance. The results showed that both leadership and compensation had a positive and significant effect on employee performance, both partially and simultaneously. These findings indicate that better leadership practices and more appropriate compensation contribute to higher levels of employee performance. Furthermore, the coefficient of determination (R Square) was 0.884, indicating that 88.4% of the variation in employee performance could be explained by the leadership and compensation variables, while the remaining 11.6% was influenced by other factors not included in the research model.